Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Against the odds? Keeping a nontraditional division of domestic work after first parenthood in Spain. - Dominguez-Folgueras, Marta; Jurado-Guerrero, Teresa; Botía-Morillas, Carmen (Journal of Family Issues, 2018)
This article analyzes changes in the division of routine domestic work after first parenthood. We wanted to know whether and how it was possible for couples to resist the trend toward traditionalization that has been shown in the literature. To do so, we analyze semistructured interviews with 27 Spanish couples who were expecting their first child in 2011 and interviewed them again in 2013. The couples were selected from a bigger sample because of their nontraditional practices preparenthood. Our results show that 17 of them were able to maintain a nontraditional division of domestic work, whereas 10 traditionalized. In our analysis, relative resources and time availability did not sufficiently explain the changes in the division of work, but specific characteristics of the division of work before childbirth—men’s active participation, the routinization of tasks, and flexible standards—emerged as key factors to resist the trend toward more traditional arrangements. © 2017, © The Author(s) 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; division sexuelle du travail; espagne; europe; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique

Un autre regard 2 : fallait demander - Emma (Massot éditions, 2018)
Un autre regard Trucs en vrac pour voir les choses autrement Jusqu'en 2010, je suis une petite citoyenne modèle. J'étudie, puis je travaille, je soutiens des associations charitables, je vote, et je trie soigneusement mes emballages. Je vois bien que le monde va mal et je pense que c'est à cause des gens gui n'étudient pas, ne travaillent pas, ne soutiennent pas d'associations, ne votent pas, et ne trient pas leurs emballages. À 30 ans, je passe, en partie, du côté de celles et ceux que le système abîme. Je réalise que loin d'avoir contribué à améliorer ma société, j'ai participé à son délitement. Je m'éveille politiquement. Ce monde que je me mets à voir différemment, je veux, le révéler à tout.e.s. Alors en 2016, je commence à dessiner mes pensées et mes découvertes, en expliquant le cheminement gui m'y a amenée. Ce livre est Le fruit d'observations et de réflexions mises en images au fil de l'actualité Une autre façon de voir notre monde pour aboutir, collectivement, à une autre façon de le faire tourner.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; bande-dessinée; charge mentale; charge émotionnelle; corps; maternité; patriarcat; projet charge mentale; périodes historiques; sexisme; systèmes d'oppressions; thématiques; travail; violences

S’organiser autrement : la prise de parole et de décision dans les organisations féministes - Meunier, Véronique (Université de Montréal, 2018)
Ce mémoire explore les processus interactionnels et les pratiques décisionnelles au sein des organisations féministes et les manières dont les participantes en font sens. Une revue de la littérature a démontré que les organisations féministes portent une attention particulière à l’inclusion des participantes dans le groupe et tentent souvent d’instaurer des rapports égalitaires entre les membres. L’observation de réunions d’une organisation sélectionnée a permis de décrire les pratiques et les stratégies utilisées par les membres. Il a été observé que plusieurs mécanismes contribuent à la création d’un climat de participation et d’échanges dans le groupe. Six entretiens semi-dirigés ont été réalisés avec des participantes de l’organisation afin de comprendre comment elles-mêmes font sens de leur expérience au sein du groupe. Il a émergé des observations que le souci d’inclusion des participantes se manifeste lors des processus de prise de décision, notamment avec la recherche de consensus. Les résultats suggèrent également que les participantes sont parfois confrontées à des contradictions entre les idéaux féministes et la pratique.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; communication; discipline; inclusion; mémoires/thèses; organisations féministes; pratiques féministes; périodes historiques; ressource en ligne; thématiques; travail; étude qualitative

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec : sommaire 2018-2 : données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Le Groupe de recherche sur l’industrie de l’humour (GRIH), la Coalition des femmes en humour (Coalition FH), avec l’appui de l’Association des professionnels de l’industrie de l’humour et de l’École nationale de l’humour, se sont unis pour un sondage historique pour l’avenir du milieu de l’humour. Afin de bien saisir le portrait réel de la situation, et de transmettre ce portrait aux décideurs de l’industrie et au public, les partenaires s’unissent pour une enquête. En effet, à ce jour, il est impossible de comparer la situation des créateurs en humour avec ceux d’autres disciplines artistiques, telles que la littérature, la danse, le théâtre ou le cinéma. Afin que les institutions culturelles comprennent davantage qui sont nos créateurs, cette enquête vise à obtenir un portrait de la population des artistes de l’humour sur le territoire québécois.
Keywords: 2000 à aujourd'hui; 2010-2019; arts; genre; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail; étude qualitative; étude quantitative

Apprendre l'usage du temps dans les familles cadres: Une enquête en immersion. - Ponsin, Annabelle (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Les pratiques de gestion de parents cadres expriment la normativité des rationalités managériales. Celles-ci renvoie à des raisonnements gestionnaires transversales (sphères privées ou publiques, familiales ou professionnelles, de loisirs) qui dessinent des rapports à soi, aux autres, et au monde (Le Texier, 2016). L’articulation des temps quotidiens (Kaufmann, 1992) et des trajectoires de vie (Bessin 2009) permet de saisir les rapports de classe, d’âge et de genre (Le Feuvre, 2006) en jeu dans ces processus. Les normes temporelles y sont « bricolées » et continuellement rejouées (Canguilhem, 1943 ; De Certeau 1994). Objectifs : J’observe la manière dont ces « temporalités managériales » sont modelées, intériorisées et transmises par les membres du couple (dans leurs vies professionnelles, parentales, conjugales), les enfants (dans leur socialisation, leur scolarité, leur mobilité) et les collectifs familiaux (dans leurs modes de gestion quotidienne). Méthodologie : L’approche qualitative s’amorce par une immersion. En tant que baby-sitter, je remplis un triple rôle : fonctionnel (pour coordonner les activités), éducatif (pour socialiser les enfants à l’enchainement de ces activités) et affectif (pour temporiser les cadences de ces rythmes). Cette immersion se complète par un dispositif d’entretiens et de carnets de bord personnalisés. Résultats : Ces foyers sont des interfaces, semi-ouvertes, de flux. La place que j’y prends est charnière pour comprendre le rôle nodal des mères et des normes éducatives dans la production, la diffusion, l’intériorisation et l’invisibilisation des normes temporelles. Conclusion : Les « modalités de construction » de ces temporalités (Elias, 1997) informent des normativités managériales qui se logent dans nos modes d’être et nos co-constructions intimes. Contribution : L’immersion dans ces territoires temporels, que j’apprivoise, est une clef pour saisir ces processus en leur cœur. Par un retour réflexif sur ma pratique itérative, cet article souligne les co-constructions familiales de normes temporelles managériales.
Keywords: 2000 à aujourd'hui; 2010-2019; care; charge mentale; discipline; europe; france; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail du care

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail